Assessment Of A Pharmacist Initiated Health Education Programme In Improving Hypertension Patients' Health Related Quality Of Life, Disease State Knowledge And Medication Adherence In Quetta City, Pakistan - Saleem, Fahad (2013)
The role of pharmacists in chronic disease state management is becoming a norm especially in the developed nations. In developing countries context, the role of pharmacists in chronic disease state management such as hypertension is yet to be fully explored. Therefore the aim of this research was to assess the impact of a pharmacist led educational intervention for improving clinical and quality of life outcomes among hypertensive patients in Quetta city, Pakistan. A mix methodological approach using both qualitative and quantitative methods was used to conduct the research. For the qualitative arm of the research, sixteen hypertensive patients were interviewed and thematic content analysis identified five major themes. In order to gain an insight of self management of hypertension, a focus group discussion was conducted with 19 hypertensive patients. The study found that the self management strategies were influenced by social sources, peers or family members with little information received from healthcare professionals. Exercise of self-management was strongly linked to the comparative advantages and disadvantages of long term medication use.